1999
DOI: 10.1007/s002210050625
|View full text |Cite
|
Sign up to set email alerts
|

Stronger occipital cortical activation to lower than upper visual field stimuli

Abstract: We recorded whole-scalp magnetoencephalographic (MEG) responses to black-and-white checkerboards to study whether the human cortical responses are quantitatively similar to stimulation of the lower and upper visual field at small, 0-6 degrees, eccentricities. All stimuli evoked strong occipital responses peaking at 50-100 ms (mean 75 ms). The activation was modeled with a single equivalent current dipole in the contralateral occipital cortex, close to the calcarine fissure, agreeing with an activation of the V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
94
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(112 citation statements)
references
References 29 publications
18
94
0
Order By: Relevance
“…The longer latency for saccades towards the lower targets is also in contrast with findings in other kinds of tasks. Indeed, lower-visual field advantage has been also observed for temporal and spatial contrast sensitivity (e.g., Skrandies, 1985aSkrandies, , 1985b, visual acuity (Millodot and Lamont, 1974), motor reaction time (e.g., Payne, 1967), visual evoked potentials latencies (Lehmann and Skrandies, 1979;Skrandies, 1987;Rudell et al, 1993;Pitzalis et al, 1997) and functional activation (Portin et al, 1999). Differences in the processing of the upper and lower retinal visual stimuli could be explained by a general superiority of the upper over the lower hemiretinal system.…”
Section: Discussionmentioning
confidence: 93%
“…The longer latency for saccades towards the lower targets is also in contrast with findings in other kinds of tasks. Indeed, lower-visual field advantage has been also observed for temporal and spatial contrast sensitivity (e.g., Skrandies, 1985aSkrandies, , 1985b, visual acuity (Millodot and Lamont, 1974), motor reaction time (e.g., Payne, 1967), visual evoked potentials latencies (Lehmann and Skrandies, 1979;Skrandies, 1987;Rudell et al, 1993;Pitzalis et al, 1997) and functional activation (Portin et al, 1999). Differences in the processing of the upper and lower retinal visual stimuli could be explained by a general superiority of the upper over the lower hemiretinal system.…”
Section: Discussionmentioning
confidence: 93%
“…In humans, the density of ganglion cells in the superior hemiretina is 60% greater than the inferior hemiretina suggesting a processing bias for visual stimuli in the lower visual Weld (Curcio and Allen 1990). Furthermore, Portin et al (1999) using magnetoencephalography have reported stronger cortical activations in the calcarine Wssure of the occipital cortex from visual stimuli in the lower visual Weld. Thus, we are particularly suited to utilize visual information obtained from the periphery in the lower visual Weld.…”
Section: Discussionmentioning
confidence: 99%
“…This frequency was chosen because it produces the largest amplitude oscillatory MEG signal (38). The lower half of the visual field was chosen for placement of the target, because filling-in has been shown to be more robust (9) and because MEG signals have been shown to be stronger for stimuli presented in the lower visual field (39). In behavioral experiments before scanning, we confirmed that the target was small enough to allow filling-in to occur, despite the pertinent flickering, but large enough to detect by using steady-state MEG responses.…”
Section: Methodsmentioning
confidence: 99%